2018
DOI: 10.1245/s10434-018-6680-6
|View full text |Cite
|
Sign up to set email alerts
|

Race and Health Disparities in Patient Refusal of Surgery for Early-Stage Pancreatic Cancer: An NCDB Cohort Study

Abstract: The percentage of patients refusing surgery for operable early-stage pancreatic cancer has been decreasing in the last decade but remains a significant issue that affects survival. Disparities in refusal of surgery are independently associated with several variables including gender, race, and insurance. To mitigate national disparities in surgical care, future studies should focus on exploring potential reasons for refusal and developing communication interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
69
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 22 publications
7
69
0
Order By: Relevance
“…Colon cancer is becoming an increasingly treatable malignancy, however oncologic surgical resection remains a critical part of treatment 4 . A proportion of patients are known to receive treatment that is not concordant with the prescribed standard of care, and prior work has shown that this disproportionally applies to vulnerable populations 9‐11 . In this study, we find that older age, Black race, lack of insurance, Medicaid, and Medicare insurance were significant predictors of refusing surgery for stage I‐III adenocarcinoma of the colon.…”
Section: Discussionmentioning
confidence: 51%
See 4 more Smart Citations
“…Colon cancer is becoming an increasingly treatable malignancy, however oncologic surgical resection remains a critical part of treatment 4 . A proportion of patients are known to receive treatment that is not concordant with the prescribed standard of care, and prior work has shown that this disproportionally applies to vulnerable populations 9‐11 . In this study, we find that older age, Black race, lack of insurance, Medicaid, and Medicare insurance were significant predictors of refusing surgery for stage I‐III adenocarcinoma of the colon.…”
Section: Discussionmentioning
confidence: 51%
“…Older age was predictive of refusing surgery in our study, with patients aged 61 or greater having significantly higher odds of refusing operative intervention compared to those aged 50 or younger. Prior work has also demonstrated that elderly patients are more likely to refuse surgery for other malignancies compared to those who are younger despite being deemed appropriate surgical candidates 9‐12 . As to why elderly patients may be refusing surgery, Rothman et al 19 found that amongst elderly patients with advanced illness, 41% of patients who refused a surgical or medical procedure reported fear of side effects as a major driving reason.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations